2022
DOI: 10.3389/fenvs.2022.834371
|View full text |Cite
|
Sign up to set email alerts
|

Back to the Future: Restoring Northern Drained Forested Peatlands for Climate Change Mitigation

Abstract: Draining peatlands for forestry in the northern hemisphere turns their soils from carbon sinks to substantial sources of greenhouse gases (GHGs). To reverse this trend, rewetting has been proposed as a climate change mitigation strategy. We performed a literature review to assess the empirical evidence supporting the hypothesis that rewetting drained forested peatlands can turn them back into carbon sinks. We also used causal loop diagrams (CLDs) to synthesize the current knowledge of how water table managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 138 publications
0
8
0
Order By: Relevance
“…For effective peatland restoration, it is necessary to consider both the hydrology of peatlands and species diversity and conservation. Peatland restoration is aimed at restoring degraded peatlands to their natural status and hydrological conditions, recovering their natural habitats, and, thus, increasing biodiversity [1,[106][107][108][109].…”
Section: Methodology For Qualitative Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…For effective peatland restoration, it is necessary to consider both the hydrology of peatlands and species diversity and conservation. Peatland restoration is aimed at restoring degraded peatlands to their natural status and hydrological conditions, recovering their natural habitats, and, thus, increasing biodiversity [1,[106][107][108][109].…”
Section: Methodology For Qualitative Assessmentmentioning
confidence: 99%
“…After rewetting, ditch systems or networks of plugged or backfilled canals are left open, and the rise in the water table results in CH 4 emissions [128]. Few studies have shown that CH 4 emissions from peatlands in northern regions have been rewetted for more than ten years [106]. For this reason, changes in GHG emissions from these peatlands remain to be discovered.…”
Section: Methods Of Peatland Rewettingmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, in Finland alone there are up to one million hectares of mire forests and fens where the drainage has not been successful in increasing the tree growth to a profitable level 18 , mainly due to lack or imbalance of nutrients in these sites. Hence, restoring forestry-drained ecosystems could result in long-term biodiversity 14 and climate benefits 19 . Indeed, restoration of forestry-drained ecosystems often succeeds in rising the water table to pristine levels 20,21 .…”
Section: Introductionmentioning
confidence: 99%